Nurturing a healthy generation of children : research gaps and opportunities - Angeles-Agdeppa, Imelda (Nestlé Nutrition Institute Workshop series, 2019)
Nutrition during infancy and childhood is the basis of an individual's health in later life. It plays an important role in metabolic programming, physiological growth, and cognition. Diet and eating behavior can provide important insights as food choices and dietary habits go hand in hand with nutrition. This book highlights the importance of childhood diets, eating behaviors, and their potential impacts on development and health. The first part examines the development of taste in infants: It shows how taste preferences are shaped in utero and throughout weaning, and how they guide the individual's later food choices. The second part focuses on what children really eat in different parts of the world. FITS (Feeding Infants and Toddlers Study) and KNHS (Kids Nutrition and Health Study) provide a glimpse into the diets of children around the world, identifying nutrition gaps and potential areas for intervention. The last part deals with breakfast and its significance as the most important meal of the day. The insights presented in this book provide valuable information for policy makers, researchers, and health care professionals.